ECOTOXIC EFFECTS OF TITANIUM DIOXIDE (TiO2) NANOPARTICLES, UPON Rattus norvegicus - SULTANA, MUBEEN; SABOOR, ABDUS (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Use of titanium dioxide, nanoparticles, in everyday products, of our life is quite common. It is used as food additive, in dairy products, tooth paste and also in various commercial products, such as paints, tiles, adhesives etc. For certain period of time its use was thought to be safe, but recent research, suggests that it has multiple deleterious implications upon human health. In this regard, the present study was attempted, to study the ecotoxic effects of titanium dioxide nanoparticles on animal physiology, with reference to liver tissue of Rattus norvegicus (Albino wister rats).Experimental animals, were subjected to three different terms of exposure such as(acute oral toxicity, 96 hrs, short term oral toxicity 28, days and sub chronic oral toxicity, 98 days)to titanium dioxide nanoparticles (TiO2). LD50, (lethal dose 50) was calculated as according to IARC 2006, and 100 nm sized particles, of TiO2was dissolved in distilled water and was fed as a single oral dose using a canula. As liver is considered as detoxifying organ, its enzymes, like Aspartate aminotransferase, (AST), Alanine aminotransferase (ALT), alkaline phosphatase (ALP) and bilirubin, are indicative of good liver functionality, they were evaluated in all the three terms of exposure. Results indicate, a significantly higher levels of all vital liver enzymes, suggesting a toxic effect of TiO2 upon liver. This study, clearly illustratesTiO2as a toxicant impacting the wellbeing of liver and therefore its indiscriminate in numerous products of everyday life, may be discouraged, or may be used with caution, if not totally stopped.